2018
DOI: 10.1177/2055102918807406
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of pain catastrophizing and mindfulness on pain intensity in women with fibromyalgia

Abstract: The objective of this study was to examine the association between facets of trait mindfulness, pain catastrophizing, and pain severity in a sample of patients with fibromyalgia. Patients with fibromyalgia completed validated baseline and diary assessments of clinical pain, mindfulness, and pain catastrophizing. Multilevel modeling analyses indicated that the daily association between catastrophizing and pain intensity was moderated by certain mindfulness facets. Our findings suggest that various aspects of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 60 publications
1
14
0
6
Order By: Relevance
“…Contrary to our expectation, lifetime meditation experience did not predict trait pain catastrophizing. Our findings corroborate other studies that reported reduced pain catastrophizing following MBI (Turner et al, 2016), and negative relations between measures of mindfulness and pain catastrophizing (Day, Smitherman, Ward, & Thorn, 2015;Dorado et al, 2018;Elvery, Jensen, Ehde, & Day, 2017;Jensen, Thorn, Carmody, Keefe, & Burns, 2018;Schutze, Rees, Preece, & Schutze, 2010). In addition, the observed pattern of pain reduction is remarkably in line with the specific cognitive attitude cultivated by mindfulness meditation that emphasizes openness to sensory experience and deliberate disengagement from cognitive-affective appraisals.…”
Section: Effect Of Meditation Expertise and Relation To Trait Charasupporting
confidence: 90%
“…Contrary to our expectation, lifetime meditation experience did not predict trait pain catastrophizing. Our findings corroborate other studies that reported reduced pain catastrophizing following MBI (Turner et al, 2016), and negative relations between measures of mindfulness and pain catastrophizing (Day, Smitherman, Ward, & Thorn, 2015;Dorado et al, 2018;Elvery, Jensen, Ehde, & Day, 2017;Jensen, Thorn, Carmody, Keefe, & Burns, 2018;Schutze, Rees, Preece, & Schutze, 2010). In addition, the observed pattern of pain reduction is remarkably in line with the specific cognitive attitude cultivated by mindfulness meditation that emphasizes openness to sensory experience and deliberate disengagement from cognitive-affective appraisals.…”
Section: Effect Of Meditation Expertise and Relation To Trait Charasupporting
confidence: 90%
“…Different degrees of mindfulness as a trait exist in the general population (unrelated to any formal training) [ 47 ]. Mindfulness-based interventions for chronic pain seem to be effective by increasing the mindfulness trait [ 48 ], thus achieving nonreactivity to cognitions, emotions, and physiological sensations, and can lead to decreased pain catastrophizing and improved quality of life [ 49 , 50 ]. Specifically, in FM, practicing mindfulness training can be beneficial by reducing perceived stress and lessening the severity of symptoms [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…PC is also a strong mediator of effects and pressure [4]. The study by Edwards et al And Taylor et al (2) stated that catastrophization of healthy vomiting behavior (health behavior) is beneficial for a person, such as exercise, which will aggravate symptoms [5]. According to Edwards et al catastrophization on how to make patients pay more attention to their pain, increase pain perception and disappoint unpleasant [5].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Edwards et al And Taylor et al (2) stated that catastrophization of healthy vomiting behavior (health behavior) is beneficial for a person, such as exercise, which will aggravate symptoms [5]. According to Edwards et al catastrophization on how to make patients pay more attention to their pain, increase pain perception and disappoint unpleasant [5]. Furthermore, catastrophization is high in fibromyalgia patients with greater activation in the brain area associated with emotion and modulation of pain money [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation